P28 The Use Of Smartphone Application (copd Assist) To Support The Implementation Of Local Primary Care Guidelines On The Management Of Patients With Copd. (10th November 2014) - Bakerly, N Diar; McCorkindale, S; Patel, G
Abstract : Introduction: Smartphone applications (apps) have become increasingly popular and offer us up-to-date access to information "on the go". Many national and international societies, medical journals and healthcare organisations develop their own apps; However using apps on a local level to promote implementation of local COPD guidelines and education has not been previously evaluated. Methods: Funding was provided by Salford's CCG innovation fund. A Smartphone app developing firm was commissioned and a development plan was agreed as follows: Close liaison with the lead respiratory physician throughout the project. A primary care focus group helped develop a Beta version for testing prior to launch. App launched as "COPD Assist" Promotion to primary care clinicians via newsletter articles, press releases, seminars, and the intranet Regular data collection on app downloads to measure usability Users' feedback and suggestions via app reviews App downloads initially restricted to Salford clinicians Objectives: Provide primary care clinicians with access to local guidelines and relevant contact details for COPD services anytime, anywhere. Provide the most up-to-date guidelines Offer clinicians access to educational material including videos (inhaler technique, spirometry, and pulmonary rehabilitation) and the opportunity to share this information with patients. Provide up to date pricing of various inhaled therapies Outcomes: COPD Assist was launched in March 2014, then publicised to all Salford's primary care clinicians supported by 5 training seminars with over 70 clinicians attending. Within 4 months following its launch, COPD assist was downloaded 622 times by different users, with an average use time of 7 min and average of 9 screens viewed per session. 52% of users have used the app more than once. Feedback was excellent, particularly around ease of use and simplicity. Conclusions: This bespoke smartphone app to support the implementation of local primary care COPD guidelines appears to be widely acceptable to users and could potentially promote these guidelines. However, more research around clinically meaningful outcomes, such as adherence to guidelines and impact on prescribing, is required to assess the true impact of such technology on the management of COPD in primary care.